Assessment of differences in the conformational flexibility of hepatitis B virus core-antigen and e-antigen by hydrogen deuterium exchange-mass spectrometry - Bereszczak, Jessica Z (Blackwell Publishing Ltd, 2014)
Hepatitis B virus core-antigen (capsid protein) and e-antigen (an immune regulator) have almost complete sequence identity, yet the dimeric proteins (termed Cp149(d) and Cp(−10)149(d), respectively) adopt quite distinct quaternary structures. Here we use hydrogen deuterium exchange-mass spectrometry (HDX-MS) to study their structural properties. We detect many regions that differ substantially in their HDX dynamics. Significantly, whilst all regions in Cp(−10)149(d) exchange by EX2-type kinetics, a number of regions in Cp149(d) were shown to exhibit a mixture of EX2- and EX1-type kinetics, hinting at conformational heterogeneity in these regions. Comparison of the HDX of the free Cp149(d) with that in assembled capsids (Cp149(c)) indicated increased resistance to exchange at the C-terminus where the inter-dimer contacts occur. Furthermore, evidence of mixed exchange kinetics were not observed in Cp149(c), implying a reduction in flexibility upon capsid formation. Cp(−10)149(d) undergoes a drastic structural change when the intermolecular disulphide bridge is reduced, adopting a Cp149(d)-like structure, as evidenced by the detected HDX dynamics being more consistent with Cp149(d) in many, albeit not all, regions. These results demonstrate the highly dynamic nature of these similar proteins. To probe the effect of these structural differences on the resulting antigenicity, we investigated binding of the antibody fragment (Fab E1) that is known to bind a conformational epitope on the four-helix bundle. Whilst Fab E1 binds to Cp149(c) and Cp149(d), it does not bind non-reduced and reduced Cp(−10)149(d), despite unhindered access to the epitope. These results imply a remarkable sensitivity of this epitope to its structural context.